Experimental investigation of hardwood air gasification in a pilot scale bubbling fluidized bed reactor and CFD simulation of jet/grid and pressure conditions. (15th July 2018) - Nam, Hyungseok; Rodriguez-Alejandro, David Aaron; Adhikari, Sushil; Brodbeck, Christian; Taylor, Steven; Johnson, James
Graphical abstract: Highlights: Pressurized pilot fluidized bed gasification was performed using hardwood pellets. CFD was used to investigate pressure drop and velocity at varied jet/grid and pressure. Jet/grid ratio at 50:50 was good for LHV, whereas that at 90:10 was good for H2. Lower ER increased the contaminant gas and tar yields with a higher LHV. Wet scrubber removed heavy chemicals (>C12 ) and high quality biochar was obtained. Abstract: A pilot scale pressurized (50 psi) fluidized bed gasification was performed to investigate the effects of the jet/grid air ratio (5:95–90:10) and equivalence ratio (ER = 0.23–0.45) on the gasification products such as syngas, tar, contaminant gas, and biochar. There was a noticeable effect of the jet/grid ratios on the syngas concentration. An increase in CO, CH4, and C2 gases was obtained at the condition closer to jet/grid = 50:50, whereas a higher jet/grid ratio favored water–gas shift reaction by increasing CO2 and H2 gases under the pressurized condition. The highest lower heating value (LHV) of 7.7 MJ/Nm 3 was obtained at the lowest ER = 0.23. Both the jet/grid ratio and ER were important parameters in determining the H2 concentration. The cold gasification and carbon conversion efficiencies were obtained as high as 66% and 94%, respectively. Also, higher temperature and ER promoted a reduction in contaminant gases as well as tar yield. Tar product yield was also reduced significantly after a wet scrubber, and the tar consisted of chemicals of a carbon number less than 13 (≤C12 ). The gasification biochar was also analyzed and showed an effective carbon sequestration property with a relatively higher surface area (105 m 2 /g). Furthermore, computational fluid dynamics simulation was performed to determine the effects of different jet/grid air ratio and pressure conditions on the hydrodynamics in the fluidized bed reactor.